2021
DOI: 10.1080/23322039.2021.1937848
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of openness on financial development in developing countries: Using a Bayesian model averaging approach

Abstract: This study investigates the influences of trade and financial openness on financial development over the period 2003-2017 from a sample of 64 developing countries, employing a Bayesian model averaging approach to take into account model uncertainty. The results demonstrate that the contribution of trade openness to financial development is important in developing economies with better institutions. However, financial openness has an insignificant positive effect on financial development. There is no evidence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 59 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…Thi Thuy and Nguyen Trong (2021) used Bayesian model averaging to explore the effects of trade and financial openness on financial development across 64 developing nations from 2003 to 2017. They found that stronger institutions in developing nations amplify the impact of trade openness on financial development, while financial openness marginally influences financial progress.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Thi Thuy and Nguyen Trong (2021) used Bayesian model averaging to explore the effects of trade and financial openness on financial development across 64 developing nations from 2003 to 2017. They found that stronger institutions in developing nations amplify the impact of trade openness on financial development, while financial openness marginally influences financial progress.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…In contrast to the earlier positionsFrancois et al (2022);Ahmed and Agha (2021) show that FD has no significant relationship with FDI as such, an effect on the FDI will not affect the FD of the economy.Trade openness (TO) is another area of globalization that has received a lot of attention recently. Several studies (such asDauda & Alhaji, 2023; John & Kyalos, 2022;Tran & Huynh, 2022;Lin et al, 2022;Lawrence & Ashenafi, (2021;Majeed et al, 2021;Ahmed & Osman, 2021;Lawrence & Ashenafi, 2021;Farah, 2020;Diem & Hoai, 2021;Ebenezer et al, 2019; Hatem & Mohamed, 2014) have indicated a direct and significant relationship between trade…”
mentioning
confidence: 99%